Answer:
z = 83 /( -c+6-t)
Step-by-step explanation:
-cz+6z= tz+83
Subtract tz from each side
-cz+6z -tz= tz-tz+83
-cz+6z- tz=83
Factor out a z
z( -c+6-t) = 83
Divide by ( -c+6-t)
z( -c+6-t)/( -c+6-t) = 83 /( -c+6-t)
z = 83 /( -c+6-t)
Step-by-step explanation:
Divide the percentage by 100. E.g 74%=64/100
Then simplify the newly made fraction,
Find the common factors,
E.g 64/100
Both can be divided by 2
32\50
Repeat simplifying step...
16\25
Till there are no more common factors
and that's the final answer...
<em>Hope you understand, if not leave a comment and I'm ready to help, please mark BRAINLIEST.</em>
Answer:
65%
Step-by-step explanation:
13/20 are recycled
We want a percent, which is out of 100
Multiply the top and bottom by 5
13*5 = 65
20*5 =100
65/100 = 65%
Answer:
y=(x^2 -2x-3)/3
Step-by-step explanation:
f(x)= √3x+4 -1
x=√3y+4 -1
(x+1)^2=(√3y+4)^2
3y+4=x^2 +2x+1
3y=x^2 +2x-3
y=(x^2 +2x-3)/3
Answer:
Therefore the Expression will be.
...As minus - minus sign becomes plus.
Step-by-step explanation:
What is six minus negative two x?
Solution:
It is the Algebraic Expression in Statement form.
Algebraic Expression is given in the form numbers and variables with the operands such as
- ' + ' Plus Sign
- ' - ' Minus Sign
- ' × ' Multiplication Sign
- ' ÷ ' Division Sign, etc.
Hence Our Statement is " six minus negative two x "
i.e. Number 6 minus sign then again a minus sign of 2x.
Therefore the Expression will be.
Also equals
...As minus - minus sign becomes plus.